Dietary and Non-Dietary Phytochemicals and Cancer - Carmela Fimognari (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The role of many phytochemicals in the modulation of the carcinogenesis process has been well documented by combining in vitro and animal studies, as well as epidemiological evidence. When acting in synergy, phytochemicals exert potential anti-cancer properties and much progress has been made in defining their many biological activities at the molecular level. However, an interesting feature in the field of phytochemicals and cancer is the role of some phytochemicals in promoting cancer development. This Special Issue of Toxins aims to provide a comprehensive look at the contribution of dietary and non-dietary phytochemicals to cancer development and at the molecular mechanisms by which phytochemicals inhibit or promote cancer. These aspects are extremely useful for the definition of efficient preventive measures against cancer.